Effect of oxygen vacancies on the band edge properties of WO3 producing enhanced photocurrents - Kalanur, Shankara S.; Yoo, Il Han; Cho, In Sun; Seo, Hyungtak (Electrochimica Acta, 2019)
In this work, we propose the synthesis and investigate the band edge properties of WO3 thin films having an optimum amount of oxygen vacancies for efficient PEC applications. A facile hydrothermal route is utilized to fabricate WO3 thin films, and a low, moderate, and high number of oxygen vacancies are introduced via annealing in O2, air, and H2, respectively. The optimum amount of oxygen vacancies in WO3 were created via the reconstructive transformation and phase transition during air annealing. Compared with the O2 and H2 annealed samples, the air annealed WO3 exhibited a significantly higher photocurrent (3.33 mA cm−2 at 2 V vs. RHE). The systematic increase in oxygen vacancies in WO3 causes a gradual decrease in the band gap and increase in the carrier density with a significant upward shift in the Fermi level and conduction and valence band edge positions. Importantly, the air annealed WO3 showed valence band expansion along with a narrowing of the band gap, increase in carrier density that giving rise to an incident photon to current efficiency of 2–3% in the far visible and IR region (600–1100 nm). Based on these data, possible channels involved in the solar light harvesting process are proposed.
Keywords: Annealed samples; Band expansion; Effect of oxygen; Flat band potential; Hydrothermal routes; Incident photon-to-current efficiencies; Reconstructive transformation; Valence band edges; Carrier density; Flat band potential; Oxygen vacancy; Valence band expansion; WO3